The Legal Position of the Papuan People's Assembly in the Review of the Papuan Special Autonomy Law at the Constitutional Court - Ali Rahman; Natasya Wulandari (Universitas Islam Negeri Raden Intan Lampung, 2026)
This article challenges the Constitutional Court's rigid formalist doctrine of legal standing by critically analysing the position of the Papuan People's Assembly (MRP) in judicial reviews of the Papua Special Autonomy Law. Currently, the Court's strict taxonomy of applicants paradoxically disenfranchises the MRP, creating a dogmatic tension between the asymmetric constitutional guarantees of indigenous rights (Article 18B of the 1945 Constitution) and actual access to constitutional justice. This study aims to expand existing standing doctrines by proposing a theoretical reconstruction of the MRP. Using normative legal research with statutory, conceptual, and case approaches, the study demonstrates that the MRP cannot be treated as a mere product of ordinary legislation. The analysis reveals that the MRP operates as a